2002
DOI: 10.1111/j.1745-9125.2002.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Counting Crime Booms Among Nations: Evidence for Homicide Victimization Rates, 1956 to 1998*

Abstract: Constructionists argue that crime booms are rare, modernizationalists predict that booms have been limited to industrializing nations, and globalizationalists claim that booms are universal among nations since World War II. We define crime booms as rates that increase rapidly and exhibit a positive sustained change in direction and use econometric methods to test for booms with homicide victimization rates for 34 nations, 1956 to I998. Twelve nations satisfied our criteria for booms-too many to support constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 43 publications
1
78
0
2
Order By: Relevance
“…The same research on post-World War II violent crime trends that seems to challenge the civilization perspective (Fukuayama 1999;LaFree and Drass 2002) can be seen as supporting the conflict perspective. There are also a growing number of regional studies which are consistent with the idea that democratization has been associated with rapidly increasing violent crime rates.…”
Section: Democracy Market Economies and Crimementioning
confidence: 91%
See 1 more Smart Citation
“…The same research on post-World War II violent crime trends that seems to challenge the civilization perspective (Fukuayama 1999;LaFree and Drass 2002) can be seen as supporting the conflict perspective. There are also a growing number of regional studies which are consistent with the idea that democratization has been associated with rapidly increasing violent crime rates.…”
Section: Democracy Market Economies and Crimementioning
confidence: 91%
“…In a recent cross-national study of homicide victimization rates in 34 countries, LaFree and Drass (2002) found that on average, homicide rates doubled during the last four decades of the twentieth century. Similarly, Fukuyama (1999:4) claims that there was a "great disruption" among western industrialized countries beginning in the 1960's which created large increases in violent crime and social disorder among most industrialized countries of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Thus in order to evaluate Durkheimian theory, time-series data are most appropriate when available (for a similar view, see LaFree & Drass, 2002). Unfortunately, valid crime and mortality data from Russia were previously unavailable due to Soviet secrecy.…”
Section: Present Investigationmentioning
confidence: 99%
“…40, 2002 Messner, 2003;Lafree and Drass, 2002. 20 Messner, 2003;Lafree and Drass, 2002. 21 Louise Shelley, "Transnational Organized Crime: The New Authoritarianism," in H. Richard Friman and Peter Andreas, eds., The Illicit Global Economy and State Power, Lanham, Md. : Rowman & Littlefield Pub., 1999. eroding political institutions and any state capacity that existed.…”
Section: Evolution Of Criminal Violencementioning
confidence: 99%